Correlation of Social Support and Mother's Self-Management of Care for a Child with A Chronic Condition - Rinik Eko Kapti; Nurona Azizah; Aprilia Nur Kasanah; Luh Putu Tania Ambara Wati; Lilik Supriati; Ari Damayanti Wahyuningrum (Journal of Nursing Practice)
Background: Mothers caring for children with chronic conditions often experience physical and psychological exhaustion, which affects their ability to master the required self-management skills. Social support is needed by mothers to master self-management of childcare with chronic conditions.